UNIVERSITY GOVERNANCE DAN KINERJA PERGURUAN TINGGI: KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Rudi Zulfikar; Yayat Ruhiat (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2018)
This study aims to analyze and provide empirical evidence of the influence of University Governance on university performance with Organization Commitment as moderating variable on private university in Serang City. This study is using purposive sampling technique with the results are 17 private university that have been registered by BAN-PT and headquarted in Serang City. Data obtained through questionnaire distributed. The analytical method used in this study are moderated regression analysis (MRA) with multiple linear analysis.Data were processed by using SPSS Statistic 22.0. Based on the test results indicate that the university governance negative affect on university performance. Commitment organization amplify university governance relationships to the university performance.